The Death of Kedis Cangak for Its Greedy (Function And Values Analysis) - Ni Made Suarningsih; I Nyoman Suwija; I Ketut Suar Adnyana; Anak Agung Gede Putera Semadi; I Gusti Agung Laksmi Swaryputri (Universitas Pendidikan Ganesha, 2023)
Balinese society is affluent in oral literature, among which there are satua or Balinese folk tales. Recently, it has been felt that the Masatua tradition has declined dramatically. The increasingly busy level of parents causes this. Entertainment on social media has defeated oral traditions. This research aims to analyze the function and value of the Death of Kedis Cangak for Its Greedy. This study uses a qualitative method. The data collection method for this research is the observation method using reading and note-taking techniques. The research results were analyzed using analytical descriptive methods and presented using informal processes. The research analysis uses the matching process. The research results show that the functions of the